Vocabulary That Is Rarely Used by People in Kuok Village, Kuok District, Kampar Regency - Elgi; Muhammad Levi; Rafika Makhiro; Riri Zelpia; Dwi riva aini fitri; restu putri nanda (Culture education and technology research (Cetera), 2024)
This article is entitled "Vocabulary That Is Rarely Used by People in Kuok Village, Kuok District, Kampar Regency". This research was carried out in Kuok Village, Kuok District, Kampar Regency. The problems raised are (1) How to use regional languages in communication among the people of Kuok Village, Kuok District, Kampar Regency (2) What are the uses of regional languages among the people of Kuok Village (3) Languages that are rarely used and often used by people in the Kuok Village area in this article The aim is to find out the use of regional languages in communication in the Kuok Village community, Kuok District, Kampar Regency, then find out the use of regional languages among the Kuok Village community, and find out languages that are rarely used and frequently used in the Kuok Village area. This article uses qualitative methods, while the data collection techniques during the research process use observation, interviews and documentation methods. The results of this research show that in this article there is some data, namely the use of regional languages in communication where the people of Kuok Village, Kuok District, Kampar Regency use the Ocu Regional Language to reflect cultural identity, traditions and linguistic diversity, strengthen social relations in the community, use Regional language among the people of Kuok Village has an important role in maintaining culture, local identity, enriching cultural life, maintaining traditions, and strengthening social ties among residents of Gumai Village, and has a language that is rarely and often used by people in the Kuok Village Area, Kuok District, Regency Kampar.